THE EFFECTIVENESS OF VIDEO-THORACOSCOPIC SURGERY FOR PULMONARY ECHINOCOCECTOMY IN CHILDREN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
During the period from 2005 to 2024, 72 children with echinococcal lung disease were operated on at the RSPCMIESC. Analysis of the results shows that echinococcal cysts with a diameter of more than 50 mm, as well as recurrent cysts complicated by suppuration, are considered as "relative" contraindications to videothoracoscopic lung echinococcectomy. In the treatment of pulmonary echinococcosis, endovideosurgical echinococcectomy is and should be a priority.